Endovascular Management of Intracranial Pial Arteriovenous Fistula with Giant Venous Varix: Case Report and Review of Literature. - Nishtha Yadav; Ambuj Kumar; Ketan Hedaoo; Sonjjay Pande (Journal of Clinical Interventional Radiology ISVIR, 2022)
Background: Intracranial pial arteriovenous fistulas (AVFs) are rare intracranial vascular malformation and their treatment is challenging because of high-flow pial supply of the lesion. We report a case of intracranial pial AVF with associated giant venous varices managed successfully by embolization. Case Description: A 25-year-old male presented with sudden onset headache and altered sensorium. Computed tomographic scan was suggestive of frontal lobar hematoma that had dissected into the third ventricle with associated intraventricular hemorrhage. Magnetic resonance imaging revealed presence of large vascular channels with the presence of multiple flow voids in bilateral frontal location. Digital subtraction angiography revealed pial fistula with arterial supply from hypertrophied left anterior cerebral artery. Treatment was done using combined coil and onyx embolization after careful analysis of angioarchitecture of the lesion using three-dimensional rotational angiogram cross-sectional reconstructions. Postprocedure angiogram revealed closure of fistula and giant varices. Conclusion: Pial AVFs with giant venous varix in adults are rare vascular malformation and understanding the angioarchitecture with exact identification of fistulous point is important to plan for surgical/endovascular management strategies. Combined strategy of embolization using coils and onyx is a safe option in such cases with giant varices.